LEGAL CHARACTERISTICS OF MEDIATION - Havrylyuk, Ruslana (Lumen Publishing House, 2019)
The article on the methodological positions of the anthropo-sociocultural approach, especially its components such as practical philosophy and material phenomenology, which are the most effective tools for perception of such an "invisible thing as the area of intersubjectivity", by M. Anri, deals with the analytic investigation of legal characteristics of mediation as an innovative method, alternative to justice, of solving interpersonal conflicts. It is substantiated that the legal characteristics of mediation are the product of both existential properties of a person and the existential arrangement of the human world. A general list of personality traits is supplemented by a provision on the attributive affiliation of human needs in benefits. It is proved that the unconditional exchange of benefits between people inevitably transforms the excess of human autonomy, being actualized in the communicative solidarity of people, and generates intrapersonal and interpersonal contradictions and conflicts. The conditional exchange of benefits between people, for its part, makes such conflicts total and especially dangerous for the existence of individuals. It is proved that mediation has a double legal nature as, firstly, it is the product of the basic (need) method of coexistence of individuals in society, and secondly, it is a system of interrelated legal obligations between them, through which a reconciled social environment is formed. On this basis mediation can be defined as mutual legal self-defense of individuals.
Keywords: Mediation; legal characteristics of mediation; excess of human autonomy; human needs in the benefits; exchange of benefits between people; egal nature of mediation